Analysis Of Treatment Outcome of Superficial Tuberculous Lymphadenitis on The Basis of Cytomorphological Features - Dutt, Nilesh C; Gupta, Anil M (National Journal of Community Medicine, 2014)
Introduction: Cases of tuberculouse lymphadenitis continue to present clinical hurdles in successful treatment outcome.This study was aimed to analyze the cytomorphological features in superficial tuberculous lymphadenitis and to analyze the treatment outcome on the basis of these features. Methods: The present study was carried out in 60 patients of superﬁcial palpable lymph nodes. All cases were subjected to fine needle aspiration of the lymphnodes. Results: Majority of patients were female and below 30 years of age. Cervical lymphnodes were most commonly involved 42(70%). It was seen that 48(80%), the lymphnodes had completely resolved.9 were considered as failures. Cases were divided into 4 groups depending on cytopathological features i.e. group I- Abscess (15), group II- Caseous necrosis(16),group III-Epitheloid grenuloma with caseation(17) and group IV Epitheloid grenuloma without caseation(12) one patient from group I and one patient from group III defaulted. On follow –up with AKT group IV patients responded best. Cases with group IV cytopatholofical features had no failures (100% cure) while group I, group II, group III had 70%, 72% and 92.3% success rate respectively. Among the necrotizing lesion the best prognosis was seen in grenuloma without caseation. Conclusion: Tuberculous lymphadenitis is more common in females with cervical lymph nodes most commonly involved.Presense of necrosis in lesions had greater chances of non- regression and failures.